From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal, 2007)
This special issue of the Review celebrates the 40th anniversary of the publication of Discovery (Glaser & Strauss, 1967) and, in so doing, is a special tribute to Barney Glaser, to his energy, his commitment and his dedication to the scholarly pursuit of knowledge and to theory that matters in everyday social life. Those of us who have had the great fortune to meet and learn from Barney are grateful for his genius, his generosity, his patience and his honesty. He's set an example that has touched each of us in a very special way. I hope that you will enjoy reading the personal perspectives shared in this issue. Among those offering tributes are internationallyrecognized Swedish scholar, Dr. Evert Gummesson, as well as members of our Peer Review Board from Australia, New Zealand, Ireland, Norway, Sweden and the United States.